2021
DOI: 10.3390/coatings11060627
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Processed Nickel Oxide and Zinc Doped Nickel Oxide Thin Films as a Hole Transport Layer for Perovskite Solar Cells

Abstract: Combustion processed nickel oxide (NiOx) thin film is considered as an alternative to the sol-gel processed hole transport layer for perovskite solar cells (PSCs). In this paper, NiOx thin film was prepared by the solution–combustion process at 250 °C, a temperature lower than the actual reaction temperature. Furthermore, the properties of the NiOx hole transport layer (HTL) in PSCs were enhanced by the incorporation of zinc (Zn) in NiOx thin films. X-ray diffraction and X-ray photoelectron spectroscopy result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Thiruchelvan et al demonstrated inverted PSCs using Zn-doped NiO x as the HTL, which maintained 80% of their initial efficiency after 108 h (4.5 days) in dark environment at room temperature with 40% relative humidity. 35 Choi et al reported Zn–Ce co-doped NiO x HTL for fabricating PSCs. The device retained 60% of initial efficiency after 120 h (5 days) in ambient environment under 70% relative humidity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thiruchelvan et al demonstrated inverted PSCs using Zn-doped NiO x as the HTL, which maintained 80% of their initial efficiency after 108 h (4.5 days) in dark environment at room temperature with 40% relative humidity. 35 Choi et al reported Zn–Ce co-doped NiO x HTL for fabricating PSCs. The device retained 60% of initial efficiency after 120 h (5 days) in ambient environment under 70% relative humidity.…”
Section: Resultsmentioning
confidence: 99%
“…Thiruchelvan et al utilized the solution-processed Zn-doped NiO x as the HTL for fabricating inverted PSCs with an average PCE of 14.67%. 35 They found that Zn doping is able to improve carrier extraction and conductivity without any negative effect on the optical properties of NiO x . Apart from single doping, some researchers select co-doping to further improve conductivity of NiO x layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They could accommodate around 90% of the metallic natural elements of the Periodic Table that stand solely or partially at the A and/or B positions without destroying the matrix structure, offering a way of correlating compositional to catalytic features. 17,18 In many applications, perovskites have shown excellent catalytic properties, including photocatalysis in NO reduction/oxidation, 19−21 solar cells, 22 CH 4 oxidation, 23 or CO oxidation. 24 Nevertheless, they are still rarely used in practice.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the combustion-synthesized Cu:NiO x resulted in better power conversion efficiency (PCE) for perovskite solar cells compare to devices containing a typical sol-gel synthesized Cu:NiO x HTL [42]. Other reports on the solution combustion synthesis of pristine and doped NiO x have applied a range of annealing temperatures for the fabrication of HTLs for efficient perovskite solar cells [43][44][45][46][47][48]. For example, Ziye Liu et al reported that the fabrication of an MA 1−y FA y PbI 3−x Cl x perovskite solar cell using solution combustion synthesized NiO x , achieving a high PCE of more than 20%.…”
Section: Introductionmentioning
confidence: 99%